Roleplayer World: Identitas Roleplayer, Relasi, dan Komunikasi - Hildawati Hildawati (Universitas Muslim Maros, 2022)
Indonesia is one of the countries with a fairly large number of K-pop fans, which is also supported by a significant number of social media users. These two aspects create a phenomenon that is popular among fans who are active on social media, named roleplayers. Roleplayer is a term that refers to K-pop fans who create a fictional figure through a new identity on social media and live their lives and roles through such identity while keeping their true identity a secret. This article focuses on the virtual communication method that roleplayer has improved from K-pop fans. This study was conducted between March and July 2022, involving 18 informants who were interviewed through Zoom Meeting and Goggle Meet. Virtual participant observation was also carried through Twitter as one of the most dynamic and crowd social media with the researcher being a roleplayer and observing the uploads of roleplayer accounts and being directly involved in their communication. The roleplay performed by K-pop fans on social media Twitter is a fictional figure with a new identity called a roleplayer. Roleplayers live a double life with different identities, one as a roleplayer who